An update to the Emergency Nursing Standards of Canadian Practice / Une mise à jour des Normes de pratique canadiennes en soins infirmiers d’urgence - Brown, Laila; Conlon, Leslie; Feist, Holly; Lacey, Paul; Leonard, Heather; McGovern, Barb; Peddle-Bolivar, Heather; Roth, Janet; Stackhouse, Sherry; Usher-Vansickle, Kandice; Vanallen, Erin (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Pappin Communications, 2025)
Over a period of almost two years, a dedicated group of NENA members, representing ED nurses from across the country reviewed the existing standards, researched standards from similar organizations, wrote a new version of the standards, and had the new edition of the standards approved by the NENA board of directors.